2020
DOI: 10.3389/fcell.2020.00360
|View full text |Cite
|
Sign up to set email alerts
|

The Keloid Disorder: Heterogeneity, Histopathology, Mechanisms and Models

Abstract: The Keloid Disorder keloid treatment. Finally, the recent change in keloid nomenclature will be discussed, which has moved away from identifying keloids solely as abnormal scars with a purely cosmetic association toward understanding keloids for the fibroproliferative disorder that they are.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
274
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(284 citation statements)
references
References 322 publications
(575 reference statements)
8
274
0
2
Order By: Relevance
“…14 Together with clinical observations, these data suggest that it would be pertinent to recognize keloids and hypertrophic scars as separate entities. [16][17][18] The principal genetically distinct collagens in keloids are types I, III and V, but type VI is also abundantly present particularly in the early stages of development. 19,20 Consequently, it has been suggested that upregulation of type VI collagen gene expression may serve as an early biomarker of the fibrotic process.…”
Section: Clini C Al and G Ene Tic Fe Ature S Of Keloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Together with clinical observations, these data suggest that it would be pertinent to recognize keloids and hypertrophic scars as separate entities. [16][17][18] The principal genetically distinct collagens in keloids are types I, III and V, but type VI is also abundantly present particularly in the early stages of development. 19,20 Consequently, it has been suggested that upregulation of type VI collagen gene expression may serve as an early biomarker of the fibrotic process.…”
Section: Clini C Al and G Ene Tic Fe Ature S Of Keloidsmentioning
confidence: 99%
“…Hydrogel-based fabrication of matrices from silk and collagen has also been used to generate a matrix in which to grow fibroblasts; however, despite many attempts to use such unique polymers, collagen-based polymers still appear to be the most physiologic and widely used despite their limitations. In a recent review of the keloid disorder, Limandjaja et al suggest that direct co-culture systems that use full-thickness keloid equivalents are the most promising models of keloid disorder but that, ultimately, there is no single universal keloid model able to be applicable to all experimental objectives 18. Keloid scarring is not found in any other animal species including non-human primates.…”
mentioning
confidence: 99%
“…Keloids are common in African, Spanish, and Asian populations, with an incidence ranging from 4.5 to 16%, and cause itching, pain, and a burning sensation (Niessen et al, 1999). Keloids can occur within years, and more likely after an inciting stimulus such as dermal injury or an inflammatory process (Limandjaja et al, 2020); however, they are most often found on the chest, shoulders, upper back, and back of the neck, where skin tension is higher than in other areas of the body (Ogawa et al, 2012;Liu et al, 2020). In addition, keloids tend to occur on the earlobes as a result of ear piercing, burns, or surgical procedures.…”
Section: Fibrosis Keloids and Hypertrophic Scarsmentioning
confidence: 99%
“…Keloids may recur, are associated with pain and pruritus, and are disfiguring (1). Numerous pathophysiologic processes have been investigated (1)(2)(3), including hypoxic (4,5), mechanical tension (6,7), and inflammatory etiologies (8)(9)(10)(11)(12). In addition, genetic studies have identified certain susceptibility loci, including inflammationrelated genes, to be significantly associated with keloids (13)(14)(15)(16)(17)(18)).…”
Section: Introductionmentioning
confidence: 99%